Research Progress on Regulatory Mechanism of Ubiquitin Modification on Warburg Effect in Malignant Tumors - WANG Fengli; HU Jing (Zhongliu Fangzhi Yanjiu, 2022)
Ubiquitin modification and Warburg effect play an important role in the occurrence and development of tumors. The process of tumor ubiquitin modification is closely related to glycolysis, that is, ubiquitin modification in tumor cells can regulate the expression level of substrate proteins related to Warburg effect, then regulate tumor progression and the treatment of drug-resistance. This paper reviews the regulation mechanism of ubiquitin modification of proteins on Warburg effect in tumor cells.